Spontaneous Rupture of Leiomyoma Diagnosed Preoperatively with Noncontrast Computed Tomography - Angel Shan; Rahana Harjee; Patrick McLaughlin; Edward C. Jones; Mohamed A. Bedaiwy (Hindawi Limited, 2020)
Background. Spontaneous rupture of benign uterine fibroids is extremely rare and has been associated with fibroid degeneration. It can cause acute intraperitoneal bleeding requiring immediate surgical intervention. Case. A previously healthy 50-year-old, Caucasian, nullipara presented with syncope, hemodynamic instability, and an acute abdomen. Noncontrast computed tomography images showed a positive sentinel clot sign in the pelvis as well as a large uterine fibroid with internal hyperdense clot suggesting acute rupture. Urgent laparotomy and hysterectomy confirmed a ruptured, actively bleeding, uterine fibroid with final pathological diagnosis of a benign leiomyoma. Conclusion. Prompt diagnosis and emergency surgical intervention were necessary to control acute hemorrhage from a ruptured uterine fibroid. Noncontrast computed tomography is an important adjunct to contrast-enhanced computed tomography and was vital for diagnosis in this case.